2020
DOI: 10.1111/andr.12811
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2, testosterone and frailty in males (PROTEGGIMI): A multidimensional research project

Abstract: Preliminary published data depicts a much greater prevalence of malewith laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) referred for intensive care unit admission and severe sequelae in several countries. In this context, males seem to not only be more susceptible to the infection compared to female subjects, at least in western countries, but their case fatality rate attributable to SARS-CoV-2 infection is also highest. Therefore, we may speculate that the different hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 23 publications
1
64
0
2
Order By: Relevance
“…Males have been shown to be overrepresented among those severely affected by COVID-19, which remained significant after adjustments for age, body mass index (BMI), and presence of comorbidities [80,81]. This consistent observation finds plausibility in the active participation of the androgen-driven TMPRSS2 to facilitate SARS-CoV-2 cell entry.…”
Section: Of Moderate Relevancementioning
confidence: 85%
“…Males have been shown to be overrepresented among those severely affected by COVID-19, which remained significant after adjustments for age, body mass index (BMI), and presence of comorbidities [80,81]. This consistent observation finds plausibility in the active participation of the androgen-driven TMPRSS2 to facilitate SARS-CoV-2 cell entry.…”
Section: Of Moderate Relevancementioning
confidence: 85%
“…In recent study, abiraterone was shown to inhibit in vitro SARS-CoV-2 activity, demonstrating another potential treatment for COVID-19 [ 42 ]. The scientific community is racing against time in search of a cure for COVID-19 and collaborative effort s are called upon to gather as much data and samples as possible to elucidate the sex disparity observed in disease outcomes [ 43 ]. A recent study of abiraterone demonstrated the ability to decrease viral load by about 70%.…”
Section: Current Clinical Trials That Address Sex Hormone Treatment Omentioning
confidence: 99%
“…In some cases, concentrations for men were lower, while in others they were higher.Since sex hormones exert specific effects on male and female immunocompetence at both the cellular and the molecular level, it is not surprising to find differences in immune and inflammatory biomarkers between men and women. For example, estrogen receptors are found in most cells of the innate and adaptive immune system including T cells, B cells, neutrophils, macrophages, dendritic cells, and natural killercells, while androgen receptors are prominent in T and B lymphocytes (Fish, 2008).Others also speculate that the different hormonal milieu could have a profound pathophysiological role in SARS-CoV-2 infection, with endogenous testosterone leaving men more prone to develop more serious complications related to the SARS-CoV-2 infection (Salonia et al, 2020).Given the range of findings and testosterone's multifaceted role in an intricate system, at this time perhaps all one can conclude is that testosterone can modulate the immune system. While in general testosterone causes a less robust immune response and estrogen helps females mount stronger immune responses, the more robust immune response in females may also lead to immunopathology resulting in fatal outcomes.Exactly how and if sex hormones positively or negatively affect outcomes in the milieu of COVID-19 remains uncertain and represents an area of future inquiry.…”
Section: Sex Hormonesmentioning
confidence: 99%